Enrique Colom Costa, Dios y el obrar humano, ediciones Universidad de Navarra, S. A., Pamplona 1976, 201 pp. - Derisi, Octavio Nicolás (1981)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina